(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
On the base of 2,3,4,5-tetrahydro- and 2,5-dihydro-4,5,5-trimethyl-2-oxofuran-3-carbonic acids were synthesized aniline, morpholine, piperidine and pyridinium salts. Antimicrobial activity of synthesized salts was studied and its dependence on the structure of synthesized salts was revealed.